Pengaruh Trichoderma harzianum dan Nano Silika Terhadap Penyakit Moler dan Produksi Bawang Merah - Ishlah, Muhammad Akhlishil; Kristanto, Budi Adi; Kusmiyati, Florentina (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
Twisted disease is one of the important diseases that can decrease shallot yield.The purpose of this experiment was to examine the effect of the interaction Trichoderma harzianum and nano silica on twisted disease and shallot yield. The research was conducted in Platar, Mangunjiwan, Demak and the Laboratory of Ecology and Plant Production, Faculty of Animal and Agriculture Science, Undip, on April – Agustus 2022. The experimental design used factorial completely randomized design with three replications. The first factor was T. harzianum consisted of three levels (P0 = 0 (control), P1 = 10, and P2 = 20 g plant-1). The second factor was nano silica concentration with four levels (S0 = 0, S1 = 1000, S2 = 2000, and S3 = 3000 ppm). The results showed that application of T. harzianum 20 g plant-1 or nano silica 3000 ppm had the lowest disease intensity 2,74 % and 2,48 % observed at 20 days after planting and 11,81 % and 10,81 % observed at 40 DAP. Combination T. harzianum 20 g plant-1 and nano silica 3000 ppm resulted in the highest yield parameters which were tuber diameter (2,370 cm), number of tubers (6 tubers), tuber fresh weight (36,2 g), and tuber dry weight (28,7 g). Treatments of T. harzianum and nano silica did not significantly affect the infection rate and number of leaves, but application of T. harzianum 20 g plant-1 and nano silica 3000 ppm showed a decrease in twisted disease intensity and the highest shallot yield.